PLOT STRUCTURES IN A NOVEL ENTITLED THE SUITCASE KID WRITTEN BY JACQUELINE WILSON:An Analysis with A Narratological Approach - Rusdi, Siti Aisyah Saraswati (2016)
This present research aims to analyze the plot structures in Jacqueline Wilson's novel entitled The Suitcase Kid (1992) by using Narratology. This qualitative research focuses on the plot of the story in order to analyze how the plot of the story is structured in the novel and to construct the meaning that can be made from the structure of the plot. The findings of this research reveal that the plot of the story is structured like a tree. The plot is developed by a major plot which gives ways for five interrelated plots and forms a story with branching plots. The finding indicates that there are two potential meaning which originated by the structure of the plot. Firstly, the story with branching plots elevates the level of suspense to the reader. Secondly, the set of events in the novel indicates that The Suitcase Kid can be considered as a Bildungsroman novel. Keywords: Plot structures, narratology, bildungsroman Penelitian ini bertujuan untuk menganalisa struktur plot yang terdapat di dalam novel karya Jacqueline Wilson berjudul The Suitcase Kid (1992) dengan menggunakan teori Narratology. Penelitian kualitatif ini berfokus pada plot cerita sebagai tujuan untuk menganalisa bagaimana plot cerita disusun di dalam novel dan untuk membangun makna yang dihasilkan dari struktur plot cerita tersebut. Hasil penelitian ini membuktikan bahwa plot cerita disusun menyerupai sebuah pohon. Plot cerita ini dibangun oleh sebuah plot utama dan menciptakan lima plot lainnya yang saling berhubungan sehingga membangun sebuah cerita yang mempunyai percabangan plot. Hasil penelitian menunjukkan bahwa terdapat dua makna yang dihasilkan oleh susunan plot cerita tersebut. Pertama, sebuah cerita yang mempunyai percabangan plot dapat meningkatkan tingkat ketegangan bagi para pembaca. Kedua, kumpulan peristiwa yang terjadi di dalam cerita tersebut menunjukkan bahwa The Suitcase Kid dapat dianggap sebagai sebuah novel Bildungsroman. Kata Kunci: Struktur plot, narratology, bildungsroman